Next Article in Journal
A Unified Asymptotic Theory of Supersonic, Transonic, and Hypersonic Far Fields
Next Article in Special Issue
New Developments in Geometric Function Theory
Previous Article in Journal
Fractional Clique Collocation Technique for Numerical Simulations of Fractional-Order Brusselator Chemical Model
Previous Article in Special Issue
Geometric Study of 2D-Wave Equations in View of K-Symbol Airy Functions

Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# Certain New Class of Analytic Functions Defined by Using a Fractional Derivative and Mittag-Leffler Functions

1
Department of Basic Science, College of Science and Theoretical Studies, Saudi Electronic University, Riyadh 11673, Saudi Arabia
2
Department of Mathematics, Abbottabad University of Science and Technology, Abbottabad 22500, Pakistan
3
4
Department of Mathematical Science, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Bangi 43600, Malaysia
5
Faculity of Computer Science, Arab Open University, Riyadh 11681, Saudi Arabia
*
Author to whom correspondence should be addressed.
Axioms 2022, 11(11), 655; https://doi.org/10.3390/axioms11110655
Submission received: 13 October 2022 / Revised: 14 November 2022 / Accepted: 14 November 2022 / Published: 18 November 2022
(This article belongs to the Special Issue New Developments in Geometric Function Theory)

## Abstract

:
Fractional calculus has a number of applications in the field of science, specially in mathematics. In this paper, we discuss some applications of fractional differential operators in the field of geometric function theory. Here, we combine the fractional differential operator and the Mittag-Leffler functions to formulate and arrange a new operator of fractional calculus. We define a new class of normalized analytic functions by means of a newly defined fractional operator and discuss some of its interesting geometric properties in open unit disk.
MSC:
05A30; 30C45; 11B65; 47B38

## 1. Introduction and Definitions

Let $A$ denote the class of functions $η$ of the form
$η ( z ) = z + ∑ n = 2 ∞ a n z n ,$
which are analytic in the open unit disk
$U = { z ∈ C : z < 1 }$
and satisfy the normalization condition
$η ( 0 ) = η ′ ( 0 ) − 1 = 0 .$
Furthermore, we denote by $S$ the subclass of $A$ consisting of functions of the form (1), which are also univalent in $U .$
For two functions $η , y ∈ A$, we say that $η$ subordinated to y, written as
$η ( z ) ≺ y ( z ) ,$
or equivalently
$η ( z ) = y ( k ( z ) ) ,$
where, $k ( z )$ is the Schwarz function in U along with the condition, (see [1])
$k ( 0 ) = 0 and | k ( z ) | < 1 .$
If y is univalent in U, then
$η ( z ) ≺ y ( z ) ⟺ η ( 0 ) = y ( 0 ) and η ( U ) ⊂ y ( U ) .$
The majorization of two analytic function $( η ≪ y )$ if and only if
$η ( z ) = k ( z ) y ( z ) , z ∈ U ,$
and also the coefficient inequality is satisfied
$a n ≤ b n .$
There exists a wide formation between the subordination and majorization [2] in U for established different classes including the the class of starlike functions $( S * )$:
$Re z η ′ ( z ) η ( z ) > 0 , z ∈ U$
and convex functions $( C )$:
$1 + Re z η ″ ( z ) η ′ ( z ) > 0 , z ∈ U .$
Related to classes $S *$ and $C$, we define the class $P$ of analytic functions $m ∈ P$, which are normalized by
$m ( z ) = 1 + ∑ n = 1 ∞ c n z n ,$
such that
$Re m ( z ) > 0 in U and m ( 0 ) = 1 .$
The convolution $( * )$ of $η$ and y, defined by
$η * y ( z ) = ∑ n = 0 ∞ a n b n z n ,$
where,
$y ( z ) = ∑ n = 0 ∞ b n z n , ( z ∈ U ) .$
Srivastava et al. [3] geometrically explored the class of complex fractional operators (differential and integral) and Ibrahim [4] provided the generality for a class of analytic functions into two-dimensional fractional parameters in U. Number of authors used these operators to illustrate various subclasses of analytic functions, fractional analytic functions and differential equations of complex variable [5,6,7].
Definition 1.
Pochhammer symbol $( α ) n$ can be defined as:
$( α ) n = α ( α + 1 ) ⋯ ( α + n − 1 ) i f n ≠ 0$
and
$( α ) n = 1 i f n = 0 .$
Definition 2.
The $( α ) n$ can be expressed in terms of the Gamma function as:
$( α ) n = Γ ( α + n ) Γ ( α ) , n ∈ N .$
In [8], Mittag-Leffler introduced Mittag-Leffler functions $H α ( z )$ as:
$H α ( z ) = ∑ n = 0 ∞ 1 Γ ( α n + 1 ) z n , α ∈ C , Re ( α ) > 0 ,$
and its generalization $H α , β ( z )$ introduced by Wiman [9] as:
$H α , β ( z ) = ∑ n = 0 ∞ 1 Γ ( α n + β ) z n , α , β ∈ C , Re ( α ) , Re ( β ) > 0 .$
Now we define the normalization of Mittag-Leffler function $M α , β ( z )$ as follows:
$M α , β ( z ) = z Γ ( β ) H α , β ( z ) M α , β ( z ) = z + ∑ n = 2 ∞ Γ ( β ) Γ ( α n − 1 + β ) z n ,$
where, $z ∈ U$, $Re α > 0$, $β ∈ C \ 0 , − 1 , − 2 , ⋯ ) .$
A function $f ∈ A$ is called bounded turning if it satisfies the condition
$Re η ′ ( z ) > 0 .$
For $0 ≤ ν < 1 ,$ let $B v$ denote the class of functions $η$ of the form (1), so that Re$η ′ > v$ in U. The functions in $B ( v )$ are called functions of bounded turning (c.f. [1], Vol. II). Nashiro–Warschowski Theorem (see, e.g., [1], Vol. I) stated that the functions in $B v$ are univalent and also close-to-convex in U. Now recall the definition of class $R$ of bounded turning functions and can be defined as:
$R = η ∈ A : η ′ ( z ) ≺ 1 + z 1 − z , z ∈ U .$
In [3], Srivastava and Owa gave definitions for fractional derivative operator and fractional integral operator in the complex z-plane $C$ as follows:
The fractional integral of order $δ$ is defined for a function $η ( z ) ,$ by
$I z δ η ( z ) ≡ I z − δ η ( z ) = 1 Γ δ ∫ 0 z z − t δ − 1 η ( t ) d ( t ) , δ > 0 .$
The fractional derivative operator $D z$ of order $δ$ is defined by
$D z δ η ( z ) = D z I z 1 − δ η ( z ) = 1 Γ 1 − δ D z ∫ 0 z η ( t ) z − t δ d ( t ) , 0 ≤ δ < 1 .$
where, the function $η ( z )$ is analytic in the simply-connected region of the complex z-plane $C$ containing the origin, and the multiplicity of $z − t − δ$ is removed by requiring log$z − t$ to be real when $z − t > 0 .$
Let $δ > 0$ and m be the smallest integer, and the extended fractional derivative of $η ( z )$ of order $δ$ is defined as:
$D z δ η ( z ) = D z m I z m − δ η ( z ) , 0 ≤ δ , n > − 1 ,$
provided that it exists. We find from (4) that is
$D z δ z n = Γ n + 1 Γ n + 1 − δ z n − δ , ( 0 ≤ δ < 1 , n > − 1 )$
and
$I z δ z n = Γ n + 1 Γ n + 1 − δ z n + δ , ( 0 < δ , n > − 1 ) .$
Owa and Srivastava [10], defined the differential integral operator $Ω z δ : A → A$ in the term of series:
$Ω z δ η ( z ) = Γ 2 − δ Γ 2 z δ D z δ η ( z ) = z + ∑ n = 2 ∞ Γ 2 − δ Γ n + 1 Γ 2 Γ n + 1 − δ a n z n ,$
where,
$( δ < 2 , and z ∈ U ) .$
Here, $D z δ η ( z )$ represents the fractional integral of $η ( z )$ of order $δ$ when $− ∞ < δ < 0$ and a fractional derivative of $η ( z )$ of order $δ$ when $0 ≤ δ < 2 .$
Now, by using the definition of convolution on (3) and (5), we define fractional differential integral operator $D z δ , α , β : A → A ,$ associated with normalized Mittag-Leffler function $M α , β ( z )$ as follows:
$D z δ , α , β η ( z ) = z + ∑ n = 2 ∞ Γ 2 − δ Γ n + 1 Γ 2 Γ n + 1 − δ Γ ( β ) Γ ( α n − 1 + β ) a n z n ,$
where,
$( δ < 2 , Re α > 0 , β ∈ C \ 0 , − 1 , − 2 , ⋯ ) , z ∈ U .$
It is noted that
$D z 0 , 0 , 1 η ( z ) = η ( z ) .$
Again, by using fractional differential integral operator $D z δ , α , β$, we also define a linear multiplier fractional differential integral operator $Δ λ δ , m β α$ as follows:
$Δ λ δ , m β α η ( z ) = Δ λ δ , 1 β α Δ λ δ , m − 1 β α η ( z ) ,$
where,
$Δ λ δ , 0 β α η ( z ) = η ( z ) ,$
and
$Δ λ δ , 1 β α η ( z ) = 1 − λ D z δ , α , β η ( z ) + λ z D D z δ , α , β η ( z ) .$
It is seen from $η ( z )$ given by (1) and from (6), we have
$Δ λ δ , m β α η ( z ) = z + ∑ n = 2 ∞ A λ , δ , α , β , m , n a n z n ,$
where,
$A λ , δ , α , β , m , n = Γ 2 − δ Γ n + 1 Γ 2 Γ n + 1 − δ Γ ( β ) Γ ( α n − 1 + β ) 1 − λ + n λ m$
and
$( δ < 2 , m ∈ N , λ ≥ 0 , Re α > 0 , β ∈ C \ 0 , − 1 , − 2 , ⋯ ) , z ∈ U .$
Remark 1.
When, $δ = 0$, $α = 0 ,$ and $β = 1$, in (7) then it is reduced to the operator given by Al-Oboudi [11].
Remark 2.
For, $δ = 0 ,$ $λ = 1 ,$ $α = 0 ,$ and $β = 1$ in (7) then it is reduced to the operator given by Salagean [12].
Definition 3.
A function $η ∈ A ,$ is in the class $S λ * δ , m α β ( σ )$ if and only if
$S λ * δ , m α β ( σ ) = η ∈ A : z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) , σ ( 0 ) = 1 .$
Definition 4.
A function $η ∈ A ,$ is in the class $J λ δ , m β α ( L , M , b )$ if and only if
$J λ δ , m β α ( L , M , b ) = η ∈ A : 1 + 1 b 2 Δ λ δ , m β α η ( z ) Δ λ δ , m β α η ( z ) − β α Δ λ δ , m η ( − z ) ≺ 1 + L z 1 + M z .$
The following lemmas will be use to prove our main results.
Lemma 1
([13]). For $ϱ ∈ C$ and a positive integer $n ,$ the class of analytic functions is given by
$H ( η , n ) = η : η ( z ) = ϱ + ϱ n z n + ϱ n + 1 z n + 1 + ⋯ .$
(i) Let $l ∈ R .$ Then
$Re η ( z ) + l z η ′ ( z ) > 0 ⟶ Re η ( z ) > 0 .$
Moreover, $l > 0$ and $η ∈ H ( 1 , n ) ,$ then there is constant $δ > 0$ and $k > 0 ,$ such that
$k = k ( l , δ , n )$
and
$η ( z ) + l z η ′ ( z ) ≺ 1 + z 1 − z k ⟶ η ( z ) ≺ 1 + z 1 − z δ .$
(ii) For $η ∈ H ( 1 , n ) ,$ and for fixed real number $l > 0$ and let $c ∈ [ 0 , 1 )$, so that
$Re η 2 ( z ) + 2 η ( z ) z D η ( z ) > c ⟶ Re η ( z ) > l .$
(iii) Let $η ∈ H ( η , n ) ,$ with $Re ( η ) > 0 ,$ then
$Re η ( z ) + z η ′ ( z ) + z 2 η ″ ( z ) > 0 ,$
or for $N : U → R ,$ such that
$Re η ( z ) + z η ′ ( z ) η ( z ) N ( z ) > 0 .$
Then
$Re η ( z ) > 0 .$

## 2. Main Results

To make use of Lemma 1, first of all, we illustrate differential integral operator $Δ λ δ , m β α η ( z )$ is also bounded turning function.
Theorem 1.
Let $η ∈$ A, and
$( i ) β α Δ λ δ , m η ( z ) is of bounded turning function .$
$( i i ) Δ λ δ , m β α η ( z ) ′ ≺ 1 + z 1 − z k , k > 0 , z ∈ U .$
$( i i i ) Re Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) z > c 2 , c ∈ [ 0 , 1 ) .$
$( i v ) Re z Δ λ δ , m β α η ( z ) ″ − Δ λ δ , m β α η ( z ) ′ + 2 Δ λ δ , m β α η ( z ) z > 0 .$
$( v ) Re z Δ λ δ , m β α η ( z ) ′ / Δ λ δ , m β α η ( z ) + 2 Δ λ δ , m β α η ( z ) / z > 1 .$
Then
$Δ λ δ , m β α η ( z ) z ∈ P ( λ ) , for some λ ∈ [ 0 , 1 ) .$
Proof.
Define a function $m ( z )$ as follows:
$m ( z ) = Δ λ δ , m β α η ( z ) z , z ∈ U .$
Then computation implies that
$z m ′ ( z ) + m ( z ) = Δ λ δ , m β α η ( z ) ′ .$
From the first inequality (i), we have $Δ λ δ , m β α η ( z )$ is bounding turning function, and this give us
$Re z m ′ ( z ) + m ( z ) > 0 .$
Thus, Lemma 1, part (i) implies that
$Re m ( z ) > 0 .$
Hence (i) is proved. Accordingly, part (ii) is confirmed.
By the virtue of Lemma 1 and part (i), let $l > 0 ,$ such that $k = k ( l )$ and
$Δ λ δ , m β α η ( z ) z ≺ 1 + z 1 − z l .$
This indicates that
$Re Δ λ δ , m β α η ( z ) z > λ , λ ∈ [ 0 , 1 ) .$
Suppose that
$Re m 2 ( z ) + 2 m ( z ) . z m ′ ( z ) = 2 Re Δ λ δ , m β α η ( z ) z Δ λ δ , m β α η ( z ) ′ − Δ λ δ , m β α η ( z ) 2 z > c , c ∈ [ 0 , 1 ) .$
From the Lemma 1 and part (ii), there exists a fixed real number $l > 0$ and satisfying the condition
$Re m ( z ) > l$
and
$m ( z ) = Δ λ δ , m β α η ( z ) z ∈ P ( λ ) .$
It follows from (9) that
$Re Δ λ δ , m β α η ( z ) ′ > 0 .$
Taking the derivative (8), we then obtain
$Re m ( z ) + z m ′ ( z ) + z 2 m ″ ( z ) = Re z Δ λ δ , m β α η ( z ) ″ − Δ λ δ , m β α η ( z ) ′ + 2 Δ λ δ , m β α η ( z ) z > 0 .$
Hence, Lemma 1 (ii) implies that
$Re Δ λ δ , m β α η ( z ) z > 0 .$
The logarithmic differentiation of (8) yields
$Re m ( z ) + z m ′ ( z ) m ( z ) + z 2 m ″ ( z ) = Re z Δ λ δ , m β α η ( z ) ′ Δ q , λ δ , m β α η ( z ) + 2 Δ λ δ , m β α η ( z ) z − 1 > 0 .$
Hence, Lemma 1 (iii) implies, where $N ( z ) = 1 ,$
$Re Δ λ δ , m β α η ( z ) z > 0 .$
Now we find the upper bounds of the operator $Δ λ δ , m β α η ( z )$ by using the exponential integral in U, which provided $η ∈ S λ * δ , m α β ( σ ) .$
Theorem 2.
Let $η ∈ S λ * δ , m α β ( σ ) ,$ where $σ ( z )$ is convex in U. Then,
$Δ λ δ , m β α η ( z ) ≺ z exp ∫ 0 z σ ( ϕ ( w ) ) − 1 w d w ,$
where, $ϕ ( z )$ is analytic in U having condition
$ϕ ( 0 ) = 0 and ϕ ( z ) < 1 .$
Furthermore, for $z = ξ ,$ we have
$exp ∫ 0 1 σ ( ϕ ( − ξ ) ) − 1 w d ξ ≤ Δ λ δ , m β α η ( z ) z ≤ exp ∫ 0 1 σ ( ϕ ( ξ ) ) − 1 w d ξ .$
Proof.
By the hypothesis we received the following conclusion:
$z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) = σ ( ϕ ( z ) ) , z ∈ U ,$
and
$Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) − 1 z = σ ( ϕ ( z ) ) − 1 z .$
Consequently, integrating (11), we obtain
$log Δ λ δ , m β α η ( z ) z = ∫ 0 z σ ( ϕ ( w ) − 1 w d w .$
By the definition of subordination we attain
$Δ λ δ , m β α η ( z ) ≺ z exp ∫ 0 z σ ( Ψ ( w ) − 1 w d w .$
Hence (10) is proved.
Note that the function $σ ( z )$ convex and symmetric with respect to real axis. That is
$σ ( − ζ z ) ≤ Re σ ( Ψ ( ξ z ) ≤ σ ( ξ z ) ( 0 < ξ < 1 , z ∈ U ) ,$
then we have the inequalities
$σ ( − ξ ) ≤ σ ( − ξ z ) , σ ( ξ z ) ≤ σ ( ξ ) .$
Consequently, we obtain
$∫ 0 1 σ ( Ψ ( − ξ z ) ) − 1 ξ d ξ ≤ Re ∫ 0 1 σ ( Ψ ( ξ ) ) − 1 ξ d ξ ≤ ∫ 0 1 σ ( Ψ ( ξ z ) ) − 1 ξ d ξ .$
In the sight of Equation (12), we obtain
$∫ 0 1 σ ( Ψ ( − ξ z ) ) − 1 ξ d ξ ≤ log Δ λ δ , m β α η ( z ) z ≤ ∫ 0 1 σ ( Ψ ( ξ z ) ) − 1 ξ d ξ .$
which implies that
$exp ∫ 0 1 σ ( Ψ ( − ξ z ) ) − 1 ξ d ξ ≤ Δ λ δ , m β α η ( z ) z ≤ exp ∫ 0 1 σ ( Ψ ( ξ z ) ) − 1 ξ d ξ .$
Hence, we have
$exp ∫ 0 1 σ ( Ψ ( − ξ ) ) − 1 ξ d ξ ≤ Δ λ δ , m β α η ( z ) z ≤ exp ∫ 0 1 σ ( Ψ ( ξ ) ) − 1 ξ d ξ .$
Now we investigate the sufficient condition of $η$ to be in the class $S λ * δ , m α β ( σ ) ,$ where $σ$ is convex univalent satisfying $σ ( 0 ) = 1 .$
Theorem 3.
If $η ∈$ A, satisfies the inequality
$z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) 2 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ − z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) ,$
then, $η ∈ β α S λ * , δ , m ( σ ) .$
Proof.
Let
$m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z )$
and $m ( z ) = 1$ in the inequality
$m ( z ) + m ( z ) z m ′ ( z ) ≺ σ ( z ) ,$
then, we obtain
$m ( z ) + m ( z ) z m ′ ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) × 2 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ − z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) .$
This implies that
$m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) ,$
that is
$η ∈ S λ * , δ , m β α ( σ ) .$
Corollary 1.
Let the assumption of Theorem 3. Then,
$z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) × 1 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ − z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≪ σ ′ ( z ) .$
Proof.
Let
$m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) .$
In the view of Theorem 3, we have
$z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ σ ( z ) ,$
where, $σ ∈ C .$ Then, by [2] (Theorem 3), we obtain
$m ′ ( z ) ≪ σ ′ ( z )$
for some $z ∈ U ,$ where
$m ′ ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) 1 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ − z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) .$
It is well known that the function $σ ( z ) = e θ z ,$$1 < θ ≤ π 2$ is not convex in $U$, where the domain $σ ( U )$ is lima-bean (see [13], p. 123). Now, we can find the same result of Theorem 3 as follows:
Theorem 4.
If$η ∈$ A, it satisfies the inequality
$1 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ ≺ e θ z .$
Then,
$η ∈ S λ * δ , m α β ( e θ z ) .$
Proof.
Let
$m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) .$
After some simple computation implies that
$m ( z ) + z m ′ ( z ) m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) + z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) 1 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ − z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) = 1 + z Δ λ δ , m β α η ( z ) ″ Δ λ δ , m β α η ( z ) ′ ≺ e θ z .$
This implies that (see [13], p. 123)
$m ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) ≺ e θ z ,$
that is
$η ∈ S λ * δ , m β α ( e θ z ) .$
Theorem 5.
If$η ∈ J λ δ , m β α ( L , M , b ) ,$ then
$M ( z ) = 1 2 η ( z ) − η ( − z )$
satisfies
$1 + 1 b z Δ λ δ , m β α B ( z ) ′ Δ λ δ , m β α B ( z ) ≺ 1 + L z 1 + M z ,$
$Re z B ′ ( z ) B ( z ) ≥ 1 − ϑ 2 1 + ϑ 2 , z = ϑ < 1 .$
Proof.
Let $η ∈ J λ δ , m β α ( L , M , b ) ,$ then there occurs a function $J ( z )$ such that
$b ( J ( z ) − 1 ) = 2 z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) Δ λ δ , m β α η ( − z ) , b ( J ( − z ) − 1 ) = 2 z Δ λ δ , m β α η ( − z ) ′ Δ q , λ δ , m β α η ( − z ) − β α Δ q , λ δ , m η ( z ) .$
This confirm that
$1 + 1 b z Δ λ δ , m β α G ( z ) ′ Δ λ δ , m β α G ( z ) − 1 = J ( z ) + J ( − z ) 2 .$
However, J satisfies
$J ( z ) ≺ 1 + L z 1 + M z ,$
which is univalent, then we get
$1 + 1 b z Δ λ δ , m β α G ( z ) ′ Δ λ δ , m β α G ( z ) − 1 ≺ 1 + L z 1 + M z .$
Additionally, $G ( z )$ is starlike in z, and which implies that
$h ( z ) = z G ( z ) ′ G ( z ) ≺ 1 − z 2 1 + z 2 .$
Hence, their exist a Schwarz function $w ( z ) ,$ such that $w ( z ) ≤ z < 1 ,$ $k ( 0 ) = 0 ,$ we get
$h ( z ) ≺ 1 − w ( z ) 2 1 + w ( z ) 2 ,$
$w ( ζ ) 2 = 1 − h ( ζ ) 1 + h ( ζ ) , ζ ∈ z , ζ = r < 1 .$
A simple calculation yields
$1 − h ( ζ ) 1 + h ( ζ ) = w ( ζ ) 2 ≤ ζ 2 .$
Therefore, we get the following inequalities:
$h ( ζ ) − 1 + ζ 4 1 − ζ 4 2 ≤ 4 ζ 4 1 − ζ 4 2 , h ( ζ ) − 1 + ζ 4 1 − ζ 4 ≤ 2 ζ 2 1 − ζ 4 .$
Thus, we have
$Re z G ′ ( z ) G ( z ) ≥ 1 − ϑ 2 1 + ϑ 2 , ζ = ϑ < 1 .$
This completes the proof of Theorem 5. □
Example 1.
Let
$z η ′ ( z ) η ( z ) = z Δ λ δ , m β α η ( z ) ′ Δ λ δ , m β α η ( z ) , Δ λ δ , m β α η ( z ) = z 1 − z 2 , η ∈ A .$
Then the solution of $z η ′ ( z ) η ( z ) = 1 + z 1 − z$ is formulated as follows:
$Δ λ δ , m β α η ( z ) = z 1 − z 2 , η ∈ A .$
Moreover, the solution of the equation
$η ( z ) + z η ′ ( z ) η ( z ) = 1 + z 1 − z$
is approximated to
$η ( z ) = z 1 − z .$

## 3. Conclusions

Many researchers have discussed some applications of fractional differential operator in different areas of mathematics. In this paper, we combined fractional differential operator and the Mittag-Leffler functions and formulated a new operator of fractional calculus for a class of normalized functions in the open unit disk. We considered this operator on the two classes of analytic functions and investigated some of its applications in the field of geometric function theory. The suggested operator can be utilized to define some more classes of analytic functions or to generalize other types of differential operators.

## Author Contributions

Conceptualization, S.K. and M.D.; data curation, K.M.; formal analysis, S.K. and K.M.; investigation, M.F.K.; methodology, M.F.K. and M.D.; supervision, S.H.; visualization, S.H.; writing—original draft, S.H.; writing—review and editing, M.D. All authors have read and agreed to the published version of the manuscript.

## Funding

This study supported by UKM, under grant number: FRGS/1/2019/STG06/UKM/01/.

## Data Availability Statement

No data were used to support this study.

## Conflicts of Interest

The authors declare no conflict of interest.

## References

1. Goodman, A.W. Univalent Functions; Polygonal Publishing House: Washington, NJ, USA, 1983; Volume I–II. [Google Scholar]
2. Campbell, D.M. Majorization-subordination theorems for locally univalent functions, II. Can. J. Math. 1973, 25, 420–425. [Google Scholar] [CrossRef]
3. Srivastava, H.M.; Owa, S. (Eds.) Univalent functions, fractional calculus, and associated generalized hypergeometric functions. In Univalent Functions, Fractional Calculus, and Their Applications; John Wiley & Sons: New York, NY, USA, 1989. [Google Scholar]
4. Ibrahim, R.W. On generalized Srivastava-Owa fractional operators in the unit disk. Adv. Differ. Equ. 2011, 2011, 55. [Google Scholar] [CrossRef] [Green Version]
5. Ibrahim, R.W. Ulam stability for fractional differential equation in complex domain. Abstr. Appl. Anal. 2012, 2012, 649517. [Google Scholar] [CrossRef]
6. Ibrahim, R.W. Generalized Ulam-Hyers stability for fractional differential equations. Int. J. Math. 2012, 23, 1250056. [Google Scholar] [CrossRef] [Green Version]
7. Srivastava, H.M.; Darus, M.; Ibrahim, R.W. Classes of analytic functions with fractional powers defined by means of a certain linear operators. Integral Transform. Spec. Funct. 2011, 22, 17–28. [Google Scholar] [CrossRef]
8. Mittag-Leffler, G.M. Sur la nouvelle fonction Eα(x). Comptes Rendus Acad. Sci. Paris 1903, 137, 554–558. [Google Scholar]
9. Wiman, A. Uber den fundamentalsatz in der teorie der funktionen E(x). Acta Math. 1905, 29, 191–201. [Google Scholar] [CrossRef]
10. Owa, S.; Srivastava, H.M. Univalent and starlike generalized hypergeometric functions. Can. J. Math. 1987, 39, 1057–1077. [Google Scholar] [CrossRef]
11. Al-Oboudi, F.M. On univalent functions defined by a generalized Salagean operator. Int. J. Math. Math. Sci. 2004, 2004, 172525. [Google Scholar] [CrossRef]
12. Salagean, G.S. Subclasses of univalent functions. In Complex Analysis—Fifth Romanian-Finnish Seminar, Part 1; Lecture Notes in Mathematics; Springer: Berlin/Heidelberg, Germany, 1981; Volume 1013, pp. 362–372. [Google Scholar]
13. Miller, S.S.; Mocanu, P.T. Differential Subordinations: Theory and Applications; CRC Press: Boca Raton, FL, USA, 2000. [Google Scholar]
 Publisher’s Note: MDPI stays neutral with regard to jurisdictional claims in published maps and institutional affiliations.

## Share and Cite

MDPI and ACS Style

Khan, M.F.; Khan, S.; Hussain, S.; Darus, M.; Matarneh, K. Certain New Class of Analytic Functions Defined by Using a Fractional Derivative and Mittag-Leffler Functions. Axioms 2022, 11, 655. https://doi.org/10.3390/axioms11110655

AMA Style

Khan MF, Khan S, Hussain S, Darus M, Matarneh K. Certain New Class of Analytic Functions Defined by Using a Fractional Derivative and Mittag-Leffler Functions. Axioms. 2022; 11(11):655. https://doi.org/10.3390/axioms11110655

Chicago/Turabian Style

Khan, Mohammad Faisal, Shahid Khan, Saqib Hussain, Maslina Darus, and Khaled Matarneh. 2022. "Certain New Class of Analytic Functions Defined by Using a Fractional Derivative and Mittag-Leffler Functions" Axioms 11, no. 11: 655. https://doi.org/10.3390/axioms11110655

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.